In 6- to 8-year-old children, hair cortisol is associated with body mass index and somatic complaints, but not with stress, health-related quality of life, blood pressure, retinal vessel diameters, and cardiorespiratory fitness. (February 2017) - Gerber, Markus; Endes, Katharina; Brand, Serge; Herrmann, Christian; Colledge, Flora; Donath, Lars; Faude, Oliver; Pühse, Uwe; Hanssen, Henner; Zahner, Lukas
Highlights: One of the first studies on hair cortisol concentrations (HCCs) in young children. Higher HCCs are associated with increased BMI in girls, and somatic complaints in boys. HCCs are not associated with stress and health-related quality of life. HCCs are not associated with blood pressure, retinal vessel diameters, and fitness. Abstract: Objectives: Hair cortisol measurement has become an increasingly accepted approach in endocrinology and biopsychology. However, while in adult research hair cortisol has been proposed as a relevant biomarker for chronic stress (and its adverse consequences), studies with children are scarce. Therefore, the goal of the present exploratory study was to examine the associations between hair cortisol concentrations (HCCs), stress, and a series of health-related outcomes in a sample of Swiss first grade schoolchildren. Methods: The sample consisted of 318 children (53% girls, M age  = 7.26, SD  = 0.35). Hair strands were taken near the scalp from a posterior vertex position, and HCCs were tested for the first 3-cm hair segment. Parents provided information about their children's age, gender, parental education, children's stress (recent critical life events, daily hassles), health-related quality of life, and psychosomatic complaints. Body composition, blood pressure, retinal vessel diameters, and cardiorespiratory fitness were measured with established methods. Results: In multiple regression analyses, higher HCCs were weakly associated with increased BMI in girls (β = 0.22, p  < 0.001), whereas higher HCCs were associated with increased somatic complaints in boys (β = 0.20, p  < 0.05). No significant relationships were found between HCCs and parental reports of stress, health-related quality of life, blood pressure, retinal vessel diameters, and cardiorespiratory fitness. Conclusions: Although small significant relationships were found between HCCs, BMI and somatic complaints, the findings of this exploratory study challenge the view that HCCs can be used as a reliable biomarker of recent critical life events, daily hassles, health-related quality of life, and cardiovascular health indicators in non-clinical young children.